Tinjauan Yuridis Terhadap Penjualan Tanah pada Pihak Penjual Sedang dalam Masa Tahanan - Fadilla Wata, Audivna Putri; Tien Fitriyah, Mas Anienda (Universitas Ekasakti, 2023)
The purpose of this study is to examine the skills of the seller who is currently in detention in making a sale and purchase deed, the validity of the sale and purchase deed if the provisions of Article 22 of Government Regulation Number 37 of 1998 concerning Position Regulations for Land Deed Making Officials in the form of reading the deed are not fulfilled and how it is implemented Article 22 Government Regulation Number 37 of 1998 concerning the Position Regulations for Land Deed Officials in the field. This study uses empirical juridical legal research methods, which examines the applicable legal provisions and what actually happens in society. The results of the study show that the seller who is currently in detention is legally competent to make a Sale and Purchase Deed as long as he is an adult and not under the supervision of another person. A sale and purchase deed is valid as long as it complies with Article 1320 of the Civil Code, although it does not comply with the provisions of Article 22 of Government Regulation Number 37 of 1998 concerning Position Regulations for Officials Making Land Deeds in the form of not being read out first by the PPAT before being signed by the parties. Implementation of Article 22 of Government Regulation Number 37 of 1998 concerning Position Regulations for Officials for Making Land Deeds in the form of reading the deed before signing can be done through a Power of Attorney or direct signing to the Penitentiary. Thus, even though one of the parties is currently under detention in this case the seller, the provisions of Article 22 PP Number 37 of 1998 concerning PPAT Position Regulations will still be fulfilled, not eliminating or violating the provisions of Article 22 PP Number 37 of 1998 concerning Regulations for the Position of Making Officials Land certificate.